ANALISIS RASIO KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT SABA PRIMA KONSTRUKSI - Khoirunnisa Ramadhani; Deviana Sari (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
This study aims to determine and analyze the financial ratios to the financial performance of PT Saba Prima Konstruksi. The type of research used is quantitative research - descriptive approach. The data source used is secondary data. The data used is the financial report of PT Saba Prima Konstruksi for the period 2019 - 2023. The data analysis method used is financial ratio analysis, namely Liquidity Ratio, Solvency Ratio, Profitability Ratio and Activity Ratio. Based on the results of the analysis using financial ratios, it shows that the financial performance of PT Saba Prima Konstruksi is still less than optimal in managing the company's finances. The Liquidity Ratio is in a liquid state because it is above the average general standard of financial ratios. The Solvency Ratio and Profitability Ratio are in a less than good state because they are below the average general standard of financial ratios. The Activity Ratio is in a fairly good state because it is within the average general standard of financial ratios.